Subjetividade transcendental, liberdade e tragédia: os pressupostos do sujeito universal em Schiller - Maia, Carlos Getúlio de Freitas (2015)
This work aims to explain some important points of the German philosopher Friedrich Schiller’s thinking. I want to link central problems of his thinking, which are mostly spread in his many papers, essays and letters. Therein, I do think that there are main themes in his argumentation which he concerns with more than in other ones. As an aesthetical thinker, he has to assume art as the main problem. But he also thinks of morality, education and the knowledge subject’s grounding. Therein, my targed in this work is to find out the knowledge subject necessarily required in Schiller’s thoughts on tragedy. Thus, my investigation on Schillerian thinking tries to undestand how tragedy causes the presentation of freedom through an aesthetical piece of work. As well as what consequences that that presentation would have to its subject. Therefore, the sensient and racional nature of human beings should premise a universally valid subjetc. Which relationete itself with freedom (a Moral matter,) through tradedy (a Aesthetica matter.) Then, it would shows up a subject which conformation must be universal.